PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS LABORATORIUM VIRTUAL PADA MATERI TEORI KINETIK GAS KELAS XI SMA - Mayasari Wulandini; Zuhdi Ma’ruf; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:This study aims to produce valid virtual laboratory-based studentworksheets to be used as a medium for learning Physics in grade XI SMA on the kinetictheory of gas materials. The type of research used is Research and Development (R&D)with the ADDIE type of instructional media design model. In this study, threeexperienced physics education lecturers are carried out in the validation stage. Theresearch instrument is a questionnaire in the form of a checklist. The aspects assessedinclude aspects of content feasibility, presentation feasibility aspects, linguisticfeasibility aspects and graphic feasibility aspects. This study uses two types of data;quantitative data is obtained from the score of the validator's assessment questionnaireand qualitative one in the form of criticism and suggestions from the validator. The dataanalysis technique in this study is descriptive analysis, by calculating the validity valueof each component of the student worksheet assessment using the Aiken's V coefficientformula. The results show that virtual laboratory-based worksheets are declared validwith Aiken's V coefficient value of 0.823 with very high category.Key Words: Student Worksheets, Virtual Laboratory, Kinetic Gas Theory